Circular and linear dichroism spectroscopy of proteins - Bulheller, Benjamin M. (2009)
Circular dichroism (CD) is an important technique in the structural characterization of proteins, and especially for secondary structure determination. The CD of proteins can be calculated from first principles using the matrix method, with an accuracy that is almost quantitative for helical proteins. Thus, for proteins of unknown structure, CD calculations and experimental data can be used in conjunction to aid structure analysis. The vacuum-UV region (below 190 nm), where charge-transfer transitions have an influence on the CD spectra, can be accessed using synchrotron radiation circular dichroism (SRCD) spectroscopy. Calculations of the vacuum-UV CD spectra have been performed for 71 proteins, for which experimental SRCD spectra and X-ray crystal structures are available. The theoretical spectra are calculated considering charge-transfer and side chain transitions, which significantly improves the agreement with experiment, raising the Spearman correlation coefficient between the calculated and experimental intensity at 175 nm from 0.12 to 0.79. The influence of the different conformations used for the calculation of charge-transfer transitions is discussed in detail, focussing on the effect in the vacuum-UV. Linear dichroism (LD) provides information on the orientation of molecules but is more challenging to analyze than CD. To aid the interpretation of LD spectra, the calculation of protein LD using the matrix method is established and the results compared to experimental data. The orientations of five prototypical proteins are correctly reproduced by the calculations. Using a simplified approach, matrix method parameter sets for the nucleic bases and naphthalenediimide (NDI) have been created and are used to determine DNA/RNA conformations and to study NDI nanotubes. Finally, to make CD and LD calculations available for the scientific community in an easy-to-use fashion, the web interface DichroCalc is introduced.